Trends in Transport Intensity across Europe - Stead, Dominic (European Journal of Transport and Infrastructure Research, 2000)
Transport energy use and transport volumes have closely followed trends in economic activity over recent decades. This is not the case however for total energy consumption (across all sectors of the economy), which is not now increasing in many countries even though economic growth is still taking place. Some kind of decoupling has occurred. If this decoupling were to take place in the transport sector, it would present opportunities to reduce the consumption of energy and other resources without reducing economic competitiveness. Decoupling would also offer opportunities for the reduction of congestion and transport emissions. Consequently, there is increasing interest in how decoupling can occur. Although the decoupling of economic activity and total energy consumption has been reported for a number of European countries, the extent to which transport demand and economy activity has been decoupled has not been examined in so much detail. Using international statistical sources for all European countries and detailed data for the UK, this paper explores the extent to which transport demand is currently linked with economic indicators (such as Gross Domestic Product and Index of Sustainable Economic Welfare) and examines whether this link has changed over time. The paper contributes to understanding about the definition of transport intensity and the relationships between transport demand and economic activity in Europe